Nuove disuguaglianze di salute: il caso degli immigrati - Tognetti Bordogna, Mara (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The theme of inequalities in health conditions is taking on an increasingly important role in our society, because these inequalities are growing, and only if individuals are in good health can they be full citizens. In this paper we analyze and discuss new forms of inequality in health conditions, in relation to the presence of immigrants. In particular, we show how a society with racist tendencies contributes to increasing inequalities in health conditions, particularly as regards access to health services. We use quantitative and qualitative data.